Estudio Financiero en la Empresa Comercial D-Fasil ubicado en la Parroquia Febres Cordero - Sisa Guzmán, Diana Elizabeth (2020)
The financial study of the commercial company D-Fasil of the Febres Cordero parish allows obtaining relevant data on the internal management of the organization, where an empirical administration is identified in the process of granting credits, handling of goods and human talent, For this reason, the case study aims to analyze the financial situation of the institution, where it is related how the weaknesses described generate influence on the assets, liabilities and assets of the company. The methodology of the investigative process is structured by the types of descriptive and documentary research, which allow obtaining relevant data on the premise under analysis, the deductive method is also used, because the data obtained will allow the development of general conclusions, while the applied technique is the interview supported by means of a questionnaire directed to the owner manager of the organization, where it is obtained as a result in the horizontal financial analysis, that the Total Assets decreases by 45%, the Liabilities in 76%, and lastly, net equity shows a decrease of 45%.